MODEL MANAJEMEN PENGEMBANGAN KOMPETENSI GURU MELALUI COACHING - Mujiati Mujiati; Taufiq Harris; Furqon Wahyudi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Human resource management in education plays a strategic role in the continuous development of teacher competencies. However, teacher competency development in schools often faces obstacles in the form of suboptimal needs assessments and generic development programs. This study aims to examine the management of teacher pedagogical competency development through coaching-based needs assessment at SMPN 2 Kandangan, Kediri Regency. The study uses a qualitative approach with a focus on the implementation of coaching as a strategy for professional teacher assistance. The results show that the coaching-based needs assessment implemented since 2024 has become the basis for the preparation of the Work Plan (RHK) for teacher competency development. The HARMONI coaching innovation has proven to help teachers plan, implement, and reflect on their competency development in a more focused manner. Despite several challenges in its implementation, this approach is effective in increasing teacher engagement and supporting continuous pedagogical competency development. ABSTRAK Manajemen sumber daya manusia (SDM) pendidikan memiliki peran strategis dalam pengembangan kompetensi guru yang berkelanjutan. Namun, pengembangan kompetensi guru di sekolah masih sering menghadapi kendala berupa asesmen kebutuhan yang belum optimal dan program pengembangan yang bersifat umum. Penelitian ini bertujuan untuk mengkaji manajemen pengembangan kompetensi pedagogik guru melalui asesmen kebutuhan berbasis coaching di SMPN 2 Kandangan, Kabupaten Kediri. Penelitian menggunakan pendekatan kualitatif dengan fokus pada implementasi coaching sebagai strategi pendampingan profesional guru. Hasil penelitian menunjukkan bahwa asesmen kebutuhan berbasis coaching yang diterapkan sejak tahun 2024 menjadi dasar penyusunan Rencana Hasil Kerja (RHK) pengembangan kompetensi guru. Inovasi coaching dengan alur HARMONI terbukti membantu guru merencanakan, melaksanakan, dan merefleksikan pengembangan kompetensinya secara lebih terarah. Meskipun terdapat beberapa tantangan dalam pelaksanaannya, pendekatan ini efektif dalam meningkatkan keterlibatan guru dan mendukung pengembangan kompetensi pedagogik secara berkelanjutan.